Penggunaan Ide Zero Waste dalam Pengolahan Limbah Organik dan Anorganik untuk Meningkatkan Kualitas Lingkungan Hidup - Sa’diyah, Maidatus; Setyawan, Wawan Herry; Kumala, Akhsinatul; Arini, Aida; Salim, Muhammad Nur; Ridlwan, Burhanuddin (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
The use of zero waste ideas for processing organic and inorganic waste mainly aims to improve environmental quality. The zero-waste concept focuses on minimizing and processing organic and inorganic waste. The following are several aspects to pay attention to in implementing zero waste: 1. Waste Reduction: Reducing waste production by reducing single-use products and replacing them with reusable products. 2. Zero waste-Based Waste Management: Households must be managed by sorting, composting, and collecting goods worth selling. Trash cans must be provided to separate organic and inorganic waste.3. Use of Waste Banks: Waste banks can utilize the economic value of non-organic waste. Waste can be stored and then resold or recycled. 4. Independent Waste Management: Independent waste management can be done by composting organic waste in your household. Inorganic waste must be managed with the help of third parties such as recycling businesses. 5. Community-Based Waste Management: Schools as a community can build awareness in their community about the waste produced every day and how we play our role in reducing the dangers of waste on earth. By implementing the zero waste idea, LKSA ar-Ridlo Peterongan Jombang can improve environmental quality and reduce negative impacts on the planet. This process requires awareness and lifestyle changes that are more concerned about the environment. This program or activity aims to develop a zero-waste concept focusing on sustainably managing organic and inorganic waste. We strive to turn waste into valuable and sellable products using eco-friendly methods.